A Comparison of Digital Literacy and Student Understanding in State and Private Schools: A Focus on Pancasila Education - Ariani Songli; Wahyu Cahyana Putra; Rizky Anisa Salsabila; Budi Mulyono (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to analyze the influence of digital literacy skills on students’ understanding of the subject of Pancasila Education, as well as to compare the dynamics between state and private schools in the city of Yogyakarta. Using a quantitative approach of the ex post facto type with a correlational research design, the study involved 60 Year 11 students from State Senior High School 3 and Muhammadiyah Senior High School 4 in Yogyakarta, selected through purposive sampling. Data were collected via a questionnaire and analyzed using simple linear regression via SPSS version 31. The results indicate that digital literacy skills have a significant effect on students’ learning comprehension (Sig. < 0.001). The coefficient of determination (R-squared) value of 0.405 indicates that digital literacy contributes 40.5% to the variation in understanding of Pancasila education. Although there are differences in academic culture between state and private schools, digital literacy has proven to be a crucial cognitive tool in helping students filter information and construct knowledge independently. This finding emphasizes the importance of strengthening digital ethics and culture within the curriculum to transform the use of technology from mere entertainment into a means of reinforcing critical and responsible national values.